L’impact de la crise sur la vie des chomeurs - Vlase, Ionela (Calitatea Vieții, 2014)
This article is based on a research study upon the impact of present crisis on the life of long run unemployed. The research was conducted during August-September 2013, in several European countries, including Romania. Starting from semi-structured interviews conducted on a 15 people sample, selected based on various criteria (gender, residency, age and family context), the interviews’ analysis results showed that the crisis affects the life of Romanians, even that this fact is less reflected by statistics. This reality, hidden intentionally or by lack of accurate methods for measuring these changes, conducts to the idea that there is a deficit of social policy measures for the help of persons which are confronting a high level of poverty risk, even more deepend in the actual period of crisis.